Undergraduate Dental student’s perceptions of the effectiveness of gamified Biochemistry module - Nor Aimilia Hanim Ab Satar,; Khairul Bariah Ahmad Amin Noordin,; Siti Aishah Zainal,; Azlina Ahmad,; Norhayati Yusop, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Gamified learning activities in higher education has gained significant interest in recent years. Despite less evidence on the effectiveness, gamification of basic science subjects is suggested to benefit both educators and students compared to the conventional learning method. This cross-sectional study investigated the perception of 52 dental undergraduate students in the School of Dental Sciences, Universiti Sains Malaysia towards gamification in learning, towards the effectiveness of a biochemistry gamified teaching module, and assess the association between the effectiveness of the module and positive gamified learning outcomes. Overall, students perceived gamification to improve their understanding of topics and eased the learning process, encouraged them to participate in the discussion, and further stimulated their learning capacity through an appropriate variety of methods used. They also have positive perception towards the effectiveness of the module. A significant association was recorded between an effectively designed module and the learning environment's stimulation. In conclusion, students viewed gamification as having a positive effect on their learning progress and interpersonal skills. This study adds evidence that gamified modules are well-received by 21st-century students in delivering the course content and have huge potential for application in higher education.